Energy balance in taekwondo athletes during pre-competition - Drummond, M. D. M.; Couto, B. P.; Eufrásio, R. J. S.; Gonçalves, R.; Szmuchrowski , L. A. (Archives of Budo, 2014)
Taekwondo athletes often rigorously limit food intake for long periods prior to competitions, rapidly reducing their total body mass to fit specific weight categories. This strategy can lead to reduced performance during training and competition and impair the health of the athletes. This study aimed is the knowledge about the energy balance and micronutrient intake in taekwondo athletes during the competition period. Materials and Methods: The study sample comprised eight taekwondo athletes (17.8 ± 2.2 years, 60.9 ± 12.7 kg, and 1.8 ± 0.1 m) of both sexes with competition experience at the national and international levels. The energy balance was determined by comparing the total caloric value (TCV) and the total daily energy expenditure (TDEE), which was calculated on the basis of the metabolic equivalents of task (MET). Both measurements were performed on two non-consecutive days within 2 to 3 weeks before a target competition. TCV and TDEE were compared using the paired t test (p<0.05). Results: The results of this study indicated that the mean TCV was significantly lower than the mean TDEE (p<0.001), leading to a mean energy deficit of ¬-1246.2 ± 399.5 Kcal. Carbohydrates, lipids, and proteins accounted for 56.4 ± 3.5%, 24.12 ± 2.9%, and 19.5 ± 2.7% of the energy intake, respectively, and met the energy requirements of the athletes. Conclusions: These results indicated that taekwondo athletes had a negative caloric balance during the pre-competition period.